PENGARUH IKLIM ETIS ORGANISASI DAN STREES KERJA TERHADAP KEINGINAN BERPINDAH DENGAN KEPUASAN KERJA - Hanik Susilawati Muamarah; Indra Wijaya Kusuma (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2012)
The pupose of this study was to investigate the effect of job stress and organizational ethical climate on tax officer’s turnover intentions, with job satisfaction as intervening variable . The study was conducted to 356 tac offices ( Account representatives and tax audithors) in kanwil DJP jakarta selatan and kanwil DJP jawa timur II. The data was analyzed using structural Equation Modeling (SEM) and assisted by LISREL version 8.8 Software. The result indicated that job stress and organizational ethical climate had negative effect on job satisfaction and job satisfaction decreased turnover intention . Other result revaeled that organizational this study included the need of workload analysis and subsequent actions on strategic positions played important role in DGT, a complete evaluation to the employess and job description also should be conducted to ensure that job is well handled and match the employee capabilities.